Media Pembelajaran MP3 Dalam Meningkatkan Hafalan Al-Qur’an Siswa PAUD IT Ayah Bunda Kecamatan Merbau Labuhanbatu Utara - Mursal Aziz; Oda Kinata Banurea; Rahayu Erliyanti (Departement of Mathematics Education, 2024)
Learning media is an important part that cannot be separated in achieving learning goals. This research aims to describe MP3 learning media in improving memorization of the Al-Qur'an for PAUD IT students at Father and Mother, Merbau, North Labuhanbatu District. This research uses the classroom action research method. The results of this research are that learning carried out using the MP3 Al-Qur'an learning media becomes active, students' curiosity becomes greater so that learning activities run well and there is an increase in students' ability to memorize short letters. In the pre-action there were 8 people ( 40%) students complete individually, and 40% complete classically. In cycle I there were 13 students (65%) who completed individually, and only 65% ​​completed classically, while in cycle II there were 18 students (90%) who completed individually, and 90% classically, which is said to have completed classically. if the class average score is ≥ 65 with an achievement level of 85% of the total number of students.